A comprehensive overview of a large-scale survey on inequality perceptions (IneqPer) in Italy - Nevena Kulic; Olga Griaznova; Eleonora Clerici; Daniela Bellani; Debora Mantovani; Loris Vergolini; Francesco Scervini (Frontiers in Sociology, 2025)
The article describes the content, the methodology and the selected results deriving from a large-scale cross-sectional IneqPer survey in Italy (n = 12,000, 2024/2025) aimed at understanding the determinants of inequality perceptions and their consequences for public opinion. The dataset offers novel dimensions that include the questions on global inequality and global redistribution, individual position in global distribution, the perceived social mobility in the society, perceived gender inequality and perceptions of discrimination against immigrants, among others. Moreover, for a number of questions, it offers a possibility of cross-validation with a range of recent datasets including European Social Survey (2020), European Value Study (2017), and the International Social Survey Program (2019). The first results show that Italians indeed recognize inequality along all dimensions (e.g., socio-economic inequality, gender inequality and inequality between migrants and natives), yet they do not strongly perceive themselves as personally affected by discrimination. Moreover, although cross-validation checks reveal a strong alignment between IneqPer data and other international value surveys, respondents in the IneqPer dataset tend to express slightly more progressive views.